Extraction and characterization of inulin present in the tubers of Dahlia spp - Fuentes Campos, María E. (2013)
In this work the extraction of inulin from the tubers of Dahlia spp shown using ethanol as solvent crystallization, such tubers Lambayeque department underwent a process of heating, filtration, crystallization and drying to obtain achieving 12.85% dry inulin which made him recognition by determining some physicochemical properties. The inulin has many properties that can be exploited in several areas, the most remarkable properties those concentrating on the food industry for its ability to aid in the absorption of minerals like calcium and magnesium salts required for the body, and in the prevention of colon cancer by increasing the beneficial bacteria in the gut.